Social learning and delay in a dynamic model of price competition - Masaki Aoyagi; Manaswini Bhallay; Hikmet Gunayz (Osaka University, Institute of Social and Economic Research (ISER), 2014)
This paper studies dynamic price competition over two periods between two firms selling differentiated durable goods to two buyers who are privately informed about their types, but have valuations of the two goods dependent on the other buyer's type. The firms' pricing strategy in period 1 must take into account the buyers' incentive to wait and learn from the other buyer's decision. We construct an equilibrium based on the key observation that the expected price of either good in period 2 is the same as its price in period 1 on and off the path of play. The equilibrium is shown to be non-preemptive in the sense that even if either firm fails to make a sale in period 1, it still makes a sale with positive probability in period 2. A characterization of the equilibrium is given in terms of the probability of delay as a function of the degree of interdependence between the two buyers.
Keywords: C72; D82; 330; dynamic pricing; delay; social learning; duopoly; product differentiation; durable good; preemption; revenue management